2010
DOI: 10.1002/cbdv.200900023
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds with Added Value Prepared from Terpenes Contained in Solid Wastes from the Olive Oil Industry

Abstract: Starting from solid wastes from two-phase olive-oil extraction, the pentacyclic triterpenes oleanolic acid and maslinic acid were isolated. These natural compounds were transformed into methyl olean-12-en-28-oate (5), which then was transformed into several seco-C-ring triterpene compounds by chemical and photolytic modifications. The triene seco-products were fragmented through several oxidative procedures to produce, simultaneously, cis- and trans-decalin derivatives, both potential synthons for bioactive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The residue was dissolved into 10 mL of methanol. Soxhlet extraction has been used to extract triterpenic acids from an array of plant tissues (Kontogianni et al ., ; Parra et al ., ; Tarvainen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The residue was dissolved into 10 mL of methanol. Soxhlet extraction has been used to extract triterpenic acids from an array of plant tissues (Kontogianni et al ., ; Parra et al ., ; Tarvainen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…To contribute to environmental sustainability, a number of strategies for the revalorization of olive oil waste have been proposed based on the extraction of compounds with added value that can be used for the food and pharmaceutical industries [8,9]. Such is the case for the recovery of antioxidant polyphenols [10], terpenic acids [11], polar lipids [12], protein hydrolysates [13,14], pigments (chlorophylls and carotenoids), tocopherols, phytosterols, squalene, and aromatic compounds [8]. Examples include the use of phenolic extracts of olive pomace to enrich vegetable oils, fish burgers, fermented milk, and in the coating of edible fruits to take advantage of its antioxidant and antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately six-million tons of TPOMW are produced annually in Spain, causing serious management problems due to its phytotoxicity and its semisolid texture. , Different technologies have been proposed for the TPOMW treatment. However, this byproduct is a promising source of potentially useful compounds such as phenolic compounds, oligosaccharides, , mannitol, ,, and triterpene compounds. , This natural starting material is a significant source of triterpenes that can be used to produce chiral intermediates and may have many applications such as flavorings, fragrances, pharmaceuticals, or biocontrol agents . Among them, the main acids are oleanolic (3β-hydroxyolean-12-en-28-oic acid, 1 ), maslinic (2α,3β-dihydroxyolean-12-en-28-oic acid, 2 ), and ursolic (3β-hydroxyursan-12-en-28-oic acid, 3 ); meanwhile, the main alcohols are erythrodiol (olean-12-ene-3β,28-diol, 4 ) and uvaol (urs-12-ene-3β,28-diol, 5 ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This natural starting material is a significant source of triterpenes that can be used to produce chiral intermediates and may have many applications such as flavorings, fragrances, pharmaceuticals, or biocontrol agents. 13 Among them, the main acids are oleanolic (3β-hydroxyolean-12-en-28-oic acid, 1), maslinic (2α,3β-dihydroxyolean-12-en-28-oic acid, 2), and ursolic (3βhydroxyursan-12-en-28-oic acid, 3); meanwhile, the main alcohols are erythrodiol (olean-12-ene-3β,28-diol, 4) and uvaol (urs-12-ene-3β,28-diol, 5) (Figure 1). The studies published on these pentacyclic triterpenes have demonstrated that they display a wide variety of biological effects such as antiinflammatory, anti-HIV, analgesic, antimicrobial, hepatoprotective, and virostatic properties.…”
Section: ■ Introductionmentioning
confidence: 99%